2009
DOI: 10.1111/j.1539-6975.2009.01302.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Asymmetric Information in the Automobile Insurance Market: Dichotomous Versus Multinomial Measurement of Insurance Coverage

Abstract: In the empirical analysis of information asymmetry in automobile insurance markets, prior research used a dichotomous measurement approach that induces excessive bundling in coverage measurements and sample selection biases. To improve on the conditional correlation method for testing information asymmetry, we propose a multinomial measurement approach that constructs coverage categories at ordered multinomial levels. With this approach, we find robust evidence of information asymmetry in both coverage area an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…See also Kim et al (2009) who show similar results for Korean data and Dionne and Vanasse (1992) for Canadian data. 2039-2117(online) ISSN 2039 Mediterranean Journal of Social Sciences MCSER Publishing, Rome-Italy Vol 6 No 3 S1 May 2015 458…”
Section: The Accident Frequency Equation (Second Stage)supporting
confidence: 65%
See 1 more Smart Citation
“…See also Kim et al (2009) who show similar results for Korean data and Dionne and Vanasse (1992) for Canadian data. 2039-2117(online) ISSN 2039 Mediterranean Journal of Social Sciences MCSER Publishing, Rome-Italy Vol 6 No 3 S1 May 2015 458…”
Section: The Accident Frequency Equation (Second Stage)supporting
confidence: 65%
“…One can refers to Dahlby (1983Dahlby ( /1992 for Canada, Puelz and Snow (1994) for USA, Richaudeau (1999) for France, Saito (2006) for Japan, Kim et al (2009) for Korea, Englund (2010) for Denmark, Shi and Valdez (2011) for Singapore, and Li et al (2013) for Taiwan case. Besides a recent review article by Dionne et al (2013) which summarized the theoretical and the empirical literature concerning asymmetric information in road safety and automobile insurance market.…”
mentioning
confidence: 99%
“…For other European health insurance systems, there is 1 In the health insurance context, medical expenditure data and other medical consumption data, i.e., number of hospital stays or nights, is often used to approximate the occurrence or severity of a loss. 2 In car insurance, the majority of studies have not found evidence of adverse selection (e.g., Chiappori and Salanié, 2000;Kim et al, 2009;Dionne et al, 2001;Zavadil, 2011). Finkelstein and Poterba (2004) find evidence of adverse selection with respect to the choice of different types of annuity insurance policies but not with respect to annuity size.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of using binary measures, Richaudeau (1999) performed a count regression on number of accidents and found no evidence of adverse selection. In contrast, Kim et al (2009) showed that a multinomial measure of policyholders' coverage selection could deliver extra evidence on asymmetric information that a dichotomous indicator could not have achieved.…”
Section: Introductionmentioning
confidence: 99%